Self-concept in retired and non-retired elderly - .H. Al-jumaiali, Muayad (Journal of College of Education, 2020)
The current study aims at comparing the level of self-concept among the retired elderly and their non-retired in Baquba  city, The study also aimed to identify the differences in the self-concept of the retired elderly according to gender (male, female), The study sample consisted of (100) retirees and non-retirees aged (50) males and (50) females, The researcher used the (Maha Al-barbarie) measure to measure the self-concept of retirees, The study found that elderly non-retirees have a higher self-concept than retirees, The study also found that retired elderly males have a higher self-concept than older female retirees.
Keywords: Self-concept, retired, elderly